The Role of Islamic Education in Building the Character of the Millennial Generation - Elok Nur Affah Al Akromi (Al-Banat: Journal of Early Childhood Islamic Education, 2024)
This research aims to explore the role of Islamic education in building the character of the millennial generation in the digital era. The millennial generation faces various challenges in character building, especially due to the great influence of social media and globalization which brings new values that sometimes contradict Islamic principles. Using a qualitative approach and case study method, this study collects data through in-depth interviews and observations on students and teachers in Islamic-based schools. The results of the study show that Islamic education that emphasizes values such as honesty, responsibility, and discipline has a significant influence on shaping positive character in students. The implementation of programs such as joint tadarus, thematic studies, and other religious activities has proven to be effective in increasing the moral awareness of the millennial generation. However, this study also finds the challenges faced by students in maintaining these values in the midst of the rapid flow of digital information that is not in accordance with Islamic norms. These findings indicate that the Islamic character education strategy needs to be strengthened and adjusted to the needs of the millennial generation who live in an ever-evolving technological environment. Through the adjustment of innovative Islamic learning methods and approaches, Islamic education is expected to be able to form a generation that is not only academically intelligent, but also has noble character and is able to face global challenges. This research contributes to developing a discourse on the importance of Islamic-based character education and its relevance in the digital era